2005
DOI: 10.1088/0305-4470/38/45/008
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and non-commutativity in quantum Hall systems

Abstract: We discuss the role that interactions play in the non-commutative structure that arises when the relative coordinates of two interacting particles are projected onto the lowest Landau level. It is shown that the interactions in general renormalize the non-commutative parameter away from the non-interacting value 1 B. The effective non-commutative parameter is in general also angular momentum dependent. An heuristic argument, based on the non-commutative coordinates, is given to find the filling fractions at in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 17 publications
7
62
0
Order By: Relevance
“…The same observation appears in the framework of string theory [17,18]. Also, the quantum Hall effect well illustrates the NC quantum mechanics of space-time [19,20] (and references therein).…”
Section: Introductionsupporting
confidence: 72%
“…The same observation appears in the framework of string theory [17,18]. Also, the quantum Hall effect well illustrates the NC quantum mechanics of space-time [19,20] (and references therein).…”
Section: Introductionsupporting
confidence: 72%
“…On the other hand, interparticle interactions can renormalize the noncommutative parameter away from ( 1 B ) and thus can have affect on the filling fraction in a Quantum Hall system. Indeed, it has been demonstrated that Jain fraction for Fractional Quantum Hall Effect can be obtained in a heuristic treatment, where the electrons are attached to appropriate magnetic flux tubes [92]. Furthermore, there are certain situations where interactions can be traded with noncommutativity within a certain approximation, as can be seen by constructing a dual families of noncommutative quantum systems [129].…”
Section: Elementary Idea About Moyal Star Product In 2d and The Landamentioning
confidence: 99%
“…An example is in Condensed Matter Physics where planar systems involving a perpendicular magnetic field becomes effectively noncommutative in the lowest Landau level [53,83] (see Szabo in [1,2]) the NC parameter being identified with inverse of the magnetic field or in Anyon models [84][85][86][87][88][89][90][91]. The Landau levels also get renormalized by interparticle interactions [92] that can have nontrivial impact in fractional Quantum Hall Effect. In another development it has been shown that NC phase space algebra can influence particle dynamics directly via induced Berry curvature effects [93][94][95] in studying many Condensed Matter phenomena such as Anomalous Hall effect [53,83,[96][97][98][99], Spin Hall effect [100][101][102], models of Graphene [103] among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And in Mirza and Zarei [16] the limit for the space noncommutativity parameter is 1/ √ θ ≥ 10 −7 GeV. The authors of Harms and Micu [23], Dayi and Jellal [24] and Chakraborty et al [25][26][27][28][29][30] have studied the noncommutative quantum Hall effect, and in Harms and Micu [23] a limit of 1/ √ θ ≥ 10GeV is given. The noncommutative spin Hall effect (SHE) is discussed through a semiclassical constrained Hamiltonian and interesting results are obtained in Dayi and Elbistan [31].…”
Section: Introductionmentioning
confidence: 99%